Meeting the psychological needs of community-living stroke patients and carers: a study of third sector provision. Issue 1 (2nd January 2016) - Morris, Reg
Abstract: Purpose : To elucidate how community stroke staff in a major third sector organisation experienced their role and understood and responded to clients' psychological needs. Method : In stage 1, three focus groups of 28 staff in total were recorded, transcribed and analysed using inductive thematic analysis. Themes were authenticated by new staff groups. In stage 2, these themes informed the construction of a questionnaire delivered through the organisation's intranet by "Survey Monkey". Results : Five themes emerged from the focus groups: background and context; perceptions of clients' psychological issues; approaches to meeting psychological needs; the experience of working with psychological needs and sources of support; aspirations for future development. Four themes were used in constructing the questionnaire. Responses from 144 staff with diverse qualifications and experience were received; over half encountered 16 (of 35) psychological issues at least once per week. Stroke survivors' needs predominated over carers' needs. Skills used to address psychological problems were identified, also training and support needs and future aspirations. Support needs included information, training and access to specialist consultants. Conclusions : Psychological issues were central in the work of third sector community stroke staff; psychological skills were routinely used. Attention to means of supporting and developing these skills is required. Implications for Rehabilitation: Service leaders and commissioners should be aware that third sector community stroke staff frequently deal with a diverse range of psychological issues and perceive psychological care as central. Service leaders should consider providing training in assessment and management of mood and cognition, risk assessment and management and basic counselling. Staff should be provided with access to specialist consultation and better information about psychological aspects of referrals. There is uncertainty about key methods for supporting the delivery of psychological care (supervision, mentoring and peer support) which requires consideration.